Flame-retardant resin composition and molded article

A polyolefin-based flame-retardant resin composition using a natural inorganic filler and radical generator minimizes antimony content, ensuring effective flame retardancy and cost-effectiveness in molded articles.

JP7599268B2Active Publication Date: 2024-12-13LION IDEMITSU COMPOSITES CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2018183411
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2018-09-28
Publication Date
2024-12-13
Estimated Expiration
2038-09-28

AI Technical Summary

Technical Problem

Existing polyolefin-based compositions for flame retardancy rely heavily on antimony compounds, which are toxic and regulated, limiting their use and necessitating the development of alternative, effective, and safer flame-retardant formulations.

Method used

A flame-retardant resin composition comprising a combination of polyolefin, a natural inorganic filler, a flame retardant, and a radical generator, optimized to minimize antimony content while maintaining excellent flame retardancy, with specific ingredient ratios and properties.

Benefits of technology

The composition achieves effective flame retardancy without significant antimony, reducing costs and ensuring excellent flame resistance even in thin molded articles, while adhering to regulatory standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599268000001
    Figure 0007599268000001
  • Figure 0007599268000002
    Figure 0007599268000002
  • Figure 0007599268000003
    Figure 0007599268000003
Patent Text Reader

Abstract

To provide a flame-retardant resin composition capable of suppressing content of antimony and providing a molded body excellent in flame retardancy, and a molded body.SOLUTION: There is provided a flame-retardant resin composition containing following (A) component to (D) component, and practically no antimony, and having content of the (A) component of 39.5 mass% to 98.5 mass% based on total 100 mass% of contents of the (A) component to (C) component, content of the (B) component of 1 mass% to 60 mass% based on total 100 mass% of contents of the (A) component to (C) component, content of the (C) component of 0.5 mass% to 20 mass% based on total 100 mass% of contents of the (A) component to (C) component, and content of the (D) component of 0.01 pts.mass to 3.0 pts.mass based on total 100 pts.mass of contents of the (A) component to (C) component. (A) A polyolefin. (B) A natural inorganic filler. (C) A flame retardant. (D) A radical generator.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flame-retardant resin composition and a molded article. [Background technology]

[0002] Polyolefins are used in a wide range of fields as molding materials due to their excellent properties. However, because they are flammable, they are often required to be flame retardant when used as industrial materials.

[0003] Compositions in which an antimony compound is added to a polyolefin for the purpose of flame retardancy are known (for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2002-322322 A [Patent Document 2] JP 2012-500880 A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a flame-retardant resin composition which reduces the antimony content and enables a molded article having excellent flame retardancy to be obtained, and a molded article thereof. [Means for solving the problem]

[0006] From their findings, the inventors realized that when a flame-retardant resin composition contains an antimony compound, particularly diantimony trioxide, its applications are limited because diantimony trioxide is a poisonous and hazardous substance and is also a substance designated under the Special Measures Act. As a result of intensive research, the present inventors have found that the antimony content in a flame-retardant resin composition can be reduced by using a combination of a natural inorganic filler, a flame retardant and a radical generator at specific contents, and have completed the present invention.

[0007] According to the present invention, the following flame-retardant resin composition and the like are provided. 1. Contains the following components (A) to (D), Substantially free of antimony the content of the component (A) is 39.5% by mass or more and 98.5% by mass or less, based on 100% by mass of the total content of the components (A) to (C); the content of the (B) component is 1% by mass or more and 60% by mass or less, based on 100% by mass of the total content of the (A) components, the (B) components, and the (C) components; the content of the (C) component is 0.5% by mass or more and 20% by mass or less, based on 100% by mass of the total content of the (A) components, the (B) components, the (C) components, A flame-retardant resin composition in which the content of the component (D) is from 0.01 to 3.0 parts by mass, based on 100 parts by mass in total of the contents of the components (A), (B), and (C). (A) Polyolefin (B) Natural inorganic filler (C) Flame retardants (D) Radical generator 2. The flame-retardant resin composition according to 1, wherein the melt flow rate at 230°C of the flame-retardant resin composition is 0.01 g / 10 min or more and 100 g / 10 min or less. 3. The flame-retardant resin composition according to 1 or 2, wherein the component (A) contains polypropylene. 4. The flame-retardant resin composition according to any one of 1 to 3, wherein the melt flow rate of the component (A) at 230° C. is 0.01 g / 10 min or more and 100 g / 10 min or less. 5. The flame-retardant resin composition according to any one of 1 to 4, wherein the component (A) is polypropylene. 6. The flame-retardant resin composition according to any one of 1 to 5, wherein the component (B) comprises at least one selected from the group consisting of talc and wollastonite. 7. The component (B) is talc, 7. The flame-retardant resin composition according to any one of 1 to 6, wherein the average particle size of the (B) component is 7 μm or more and 30 μm or less. 8. The flame-retardant resin composition according to any one of 1 to 7, wherein the component (C) contains a halogen-based flame retardant. 9. The flame-retardant resin composition according to any one of 1 to 8, wherein the component (C) contains a brominated flame retardant. 10. The flame-retardant resin composition according to any one of 1 to 9, wherein the component (C) contains tris(tribromoneopentyl)phosphate. 11. The flame-retardant resin composition according to any one of 1 to 10, wherein the melting point of the component (C) is 50°C or higher and 250°C or lower. 12. The flame-retardant resin composition according to any one of 1 to 11, wherein the decomposition temperature of the component (C) is 200°C or higher and 400°C or lower. 13. The flame-retardant resin composition according to any one of 1 to 12, wherein the component (D) contains a 2,3-dimethyl-2,3-diphenyl-butane structure. 14. The flame-retardant resin composition according to any one of 1 to 13, wherein the component (D) is 2,3-dimethyl-2,3-diphenyl-butane or poly-1,4-diisopropylbenzene. 15. A molded article produced using the flame-retardant resin composition according to any one of 1 to 14. Effect of the Invention

[0008] According to the present invention, it is possible to provide a flame-retardant resin composition and a molded article which can reduce the antimony content and give a molded article having excellent flame retardancy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] In this specification, "x to y" means "greater than or equal to x and less than or equal to y." In this specification, the provisions that are considered to be preferable can be adopted arbitrarily, and it can be said that the combination of preferable provisions is more preferable. Optional constituent elements may be added as long as they do not impair the effects of the invention.

[0010] In the present specification, the "number of carbon atoms XX to YY" in the expression "a substituted or unsubstituted ZZ group having carbon atoms XX to YY" represents the number of carbon atoms when the ZZ group is unsubstituted, and does not include the number of carbon atoms of the substituent when the ZZ group is substituted. Here, "YY" is larger than "XX", and "XX" and "YY" each represent an integer of 1 or more.

[0011] In the present specification, the "number of atoms XX to YY" in the expression "a substituted or unsubstituted ZZ group having the number of atoms XX to YY" represents the number of atoms when the ZZ group is unsubstituted, and does not include the number of atoms of the substituent when the ZZ group is substituted. Here, "YY" is larger than "XX", and "XX" and "YY" each represent an integer of 1 or more.

[0012] In the case of "substituted or unsubstituted", "unsubstituted" means that it is not substituted with the above-mentioned substituents and is bonded to a hydrogen atom.

[0013] One embodiment of the flame-retardant resin composition of the present invention comprises the following components (A) to (D): the composition is substantially free of antimony, the content of the component (A) is 39.5 to 98.5 mass% (preferably 40 to 97 mass%, more preferably 52 to 96 mass%, even more preferably 59 to 95 mass%, and particularly preferably 66 to 94 mass%) based on 100 mass% of the total content of the components (A) to (C), the content of the component (B) is 1 to 60 mass% (preferably 2 to 50 mass%, more preferably 3 to 40 mass%, even more preferably 4 to 35 mass%, and particularly preferably 5 to 30 mass%) based on 100 mass% of the total content of the components (A) to (C), and the content of the component (C) is 0.5 to 20 mass% (preferably 0.7 to 10 mass%, more preferably 0.8 to 8 mass%, even more preferably 0.9 to 6 mass%, and particularly preferably 1 to 4 mass%) based on 100 mass% of the total content of the components (A) to (C), A flame-retardant resin composition in which the content of the (D) component is 0.01 to 3.0 parts by mass (preferably 0.02 to 1.0 parts by mass, more preferably 0.03 to 0.8 parts by mass, even more preferably 0.04 to 0.5 parts by mass, and particularly preferably 0.05 to 0.3 parts by mass) based on 100 parts by mass in total of the contents of the (A) to (C) components. (A) Polyolefin (hereinafter also referred to as "Component (A)") (B) Natural inorganic filler (hereinafter also referred to as "component (B)") (C) Flame retardant (hereinafter referred to as "component (C)") (D) Radical generator (hereinafter also referred to as "component (D)")

[0014] This makes it possible to reduce the antimony content and obtain a molded article with excellent flame retardancy. In addition, as an optional effect, the content of the component (C) can be reduced, which in turn can result in an optional effect of reducing costs. As an optional effect, even if the obtained molded article is thin, sufficient flame retardancy (for example, V-2 described below) can be obtained.

[0015] In one embodiment of the flame-retardant resin composition of the present invention, from the viewpoints of flame retardancy and moldability, the melt flow rate (MFR) at 230°C is preferably from 0.01 to 100 g / 10 min, more preferably from 0.1 to 90 g / 10 min, even more preferably from 1 to 70 g / 10 min, and particularly preferably from 3 to 50 g / 10 min. In one embodiment of the flame-retardant resin composition of the present invention, the MFR is measured in accordance with ASTM D-1238 (2013) under conditions of 230°C and 2.16 kg.

[0016] One embodiment of the flame-retardant resin composition of the present invention is substantially free of antimony. "Substantially free of antimony" means that the content is below the detection limit (2000 ppm) of the measuring device described below. The antimony content is measured using an EDS (energy dispersive X-ray analysis) device built into a JSM-6390LA (manufactured by JEOL Ltd.).

[0017] The polyolefin is not particularly limited, but examples thereof include homopolyolefins and olefin copolymers. Examples of polyolefins include polypropylene and polyethylene. From the viewpoint of heat resistance of the molded article, polypropylene is preferred.

[0018] Examples of the olefin include ethylene, propylene, butene, hexene, and α-olefins. Examples of the α-olefin include 1-butene, 1-hexene, 1-pentene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene.

[0019] Examples of homopolyolefins include homopolyethylene (for example, low density polyethylene, linear low density polyethylene, straight-chain low density polyethylene, high density polyethylene), homopolypropylene, etc. From the viewpoint of heat resistance of the molded article, homopolypropylene is preferred.

[0020] The olefin copolymer may be a block copolymer, a random copolymer, or a mixture thereof.

[0021] Examples of the olefin copolymer include propylene copolymers and ethylene copolymers. Examples of the propylene copolymer include copolymers of propylene and the above-mentioned olefins other than propylene. Examples of the ethylene copolymer include copolymers of ethylene and the above-mentioned olefins other than ethylene. The olefins may be used alone or in combination of two or more.

[0022] From the viewpoints of the light weight, moldability, rigidity of the molded article, and impact resistance of the molded article of the flame-retardant resin composition, the MFR of component (A) at 230°C is preferably from 0.01 to 100 g / 10 min, more preferably from 0.1 to 90 g / 10 min, even more preferably from 1 to 70 g / 10 min, and particularly preferably from 3 to 50 g / 10 min.

[0023] The MFR of component (A) at 230°C is measured in accordance with ASTM D-1238 (2013) under conditions of 230°C and 2.16 kg.

[0024] Examples of commercially available polyolefins include the polypropylene series "Prime Polypro", "Polyfine", and "Prime TPO" manufactured by Prime Polymer Co., Ltd. (e.g., product numbers "J-700GP", "J106MG", "J707G", "H700", "H-100M", "J105P", "J707P", "F-300SP", "J-466HP", and "E-105GM"); polypropylene manufactured by Idemitsu Kosan Co., Ltd. (e.g., product number "J-966HP"); various polyethylene resins manufactured by Prime Polymer Co., Ltd., such as the various series "Hi-Zex", "Neo-Zex", "Ult-Zex", "Moatec", and "Evolue" (e.g., high-density polyethylene resin, product number "2200J"); and low-density polyethylene manufactured by Tosoh Corporation (e.g., product number "Petrothene 190").

[0025] From the viewpoint of heat resistance of the molded product, the component (A) is preferably polypropylene.

[0026] The component (A) may be one type alone, or two or more types may be combined.

[0027] Examples of the component (B) include talc and wollastonite. From the viewpoint of flame retardancy, the component (B) preferably contains one or more selected from the group consisting of talc and wollastonite.

[0028] When the component (B) is talc, the average particle size (D50) is preferably from 7 to 30 μm, and more preferably from 10 to 20 μm, from the viewpoint of improving the flame retardancy of the flame-retardant resin composition. The average particle size (D50) is the diameter at which, when a powder is divided into two particles of a certain size, the larger and smaller particles are equal in amount. When component (B) is talc, the average particle size (D50) of component (B) is measured using a laser diffraction particle size distribution measuring device.

[0029] When the component (B) is wollastonite, from the viewpoint of improving the flame retardancy of the resin composition, the 400 mesh (ASTM standard) passing rate is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more, and preferably 100% or less. The 400 mesh passing rate is determined by placing a sample on a 400 mesh and sieving it through a vibrating sieve.

[0030] When component (B) is talc, the moisture content is preferably 0 to 0.5%, and more preferably 0 to 0.1%, from the viewpoints of compounding (mixing) and suppressing defects during molding. The water content of component (B) is measured using the Karl Fischer method.

[0031] When the component (B) is talc, the whiteness W value is preferably from 50 to 100%, and more preferably from 70 to 100%, from the viewpoint of the appearance of the molded product. The whiteness W value of component (B) is measured using an SM color computer.

[0032] When component (B) is talc, the apparent specific gravity is preferably 0.2 to 0.8 g / ml, and more preferably 0.3 to 0.5 g / ml, from the viewpoint of feeding during compounding. The apparent specific gravity of component (B) is measured in accordance with JIS K5101.

[0033] When the component (B) is talc, the ignition loss at 500° C. is preferably 0 to 6%, and more preferably 0 to 3%, from the viewpoint of the appearance of the molded article. When component (B) is talc, the loss on ignition at 500°C is measured using a muffle furnace.

[0034] The component (B) may be one type alone, or two or more types may be combined.

[0035] The melting point of the component (C) is preferably from 50 to 250°C, and more preferably from 100 to 200°C, from the viewpoint of flame retardancy. The melting point of component (C) is measured using a TGA (thermogravimetric analysis) / DSC (differential scanning calorimeter) 1 described below.

[0036] From the viewpoint of heat resistance, the decomposition temperature of the component (C) is preferably from 200 to 400°C, and more preferably from 250 to 350°C. The decomposition temperature of component (C) is measured using TGA / DSC1 described below.

[0037] Examples of the component (C) include halogen-based flame retardants and phosphorus-based flame retardants.

[0038] Examples of halogen-based flame retardants include 2,4,6-tris(2,4,6-tribromophenoxy)-1,3,5-triazine, brominated epoxy oligomer, ethylene bis(pentabromophenyl), ethylene bis(tetrabromophthalimide), decabromodiphenyl ether, tetrabromobisphenol A, halogenated polycarbonate, halogenated polycarbonate (co)polymer, oligomer of halogenated polycarbonate or halogenated polycarbonate (co)polymer, halogenated polystyrene, and halogenated polyolefin.

[0039] Examples of halogen-based flame retardants include bromine-based flame retardants. From the viewpoint of flame retardancy, the component (C) preferably contains a brominated flame retardant. Brominated flame retardants include: 2,2-Bis[3,5-dibromo-4-(2,3-dibromopropoxy)phenyl]propane, bis[3,5-dibromo-4-(2,3-dibromopropoxy)phenyl]sulfone, pentabromobenzyl acrylate polymer, 1,2,5,6,9,10-hexabromocyclododecane, 2,4,6-tris-(2,4,6-tribromophenoxy)-1,3,5-triazine, 2,2-bis(bromomethyl)-1,3-propanediol, tribromo-neopentyl alcohol, 2,2-bis(4-allyloxy-3,5-dibutoxy)phenyl bromophenyl)propane, BC-52 tetrabromobisphenol A, BC-58 tetrabromobisphenol A, tetrabromobisphenol A, 1,1'-[ethylenebis(oxy)]bis(2,4,6-tribromobenzene), pentabromobenzyl acrylate, tribromophenol acrylate, octabromodiphenyl ether, 2,2'-[isopropylidenebis[(2,6-dibromo-4,1-phenylene)oxy]]diethanol, N-methylhexabromodiphenylamine, TBA bisbromoethyl ether, Examples include tris(tribromoneopentyl)phosphate and tris-dibromopropyl isocyanurate. The component (C) preferably contains tris(tribromoneopentyl)phosphate or tris-dibromopropyl isocyanurate, and from the viewpoint of flame retardancy, it more preferably contains tris(tribromoneopentyl)phosphate.

[0040] The component (C) may be used alone or in combination of two or more types.

[0041] The decomposition temperature of the component (D) is preferably from 80 to 280°C, and more preferably from 120 to 240°C, from the viewpoint of flame retardancy. The decomposition temperature of component (D) is measured using TGA / DSC1 described below.

[0042] The melting point of the (D) component is preferably from 50 to 250°C, and more preferably from 100 to 200°C, from the viewpoint of flame retardancy. The melting point of component (D) is measured using TGA / DSC1 described below.

[0043] Examples of the component (D) include organic peroxides, initiators that cleave carbon-carbon bonds, and initiators that cleave nitrogen-nitrogen bonds. The component (D) preferably contains a 2,3-dimethyl-2,3-diphenyl-butane structure (also called a dicumene structure). Examples of the component (D) include 2,3-dimethyl-2,3-diphenylbutane and poly-1,4-diisopropylbenzene (tri-1,4-diisopropylbenzene). From the standpoint of flame retardancy, the component (D) is preferably 2,3-dimethyl-2,3-diphenyl-butane. From the standpoint of flame retardancy, the component (D) is preferably poly-1,4-diisopropylbenzene.

[0044] One embodiment of the flame-retardant resin composition of the present invention may further contain additives, if necessary. Examples of the additives include ultraviolet absorbers, light stabilizers, antioxidants, lubricants, crystal nucleating agents, softeners, antistatic agents, metal deactivators, antibacterial or antifungal agents, and pigments.

[0045] The ultraviolet absorbing agent is not particularly limited, but examples thereof include benzophenone-based compounds, benzotriazole-based compounds, benzoate-based compounds, polyamide polyether block copolymers (permanently antistatic). The antioxidant is not particularly limited, but examples thereof include phenol-based antioxidants, phosphorus-based antioxidants, and thioether-based antioxidants. The lubricant is not particularly limited, but examples thereof include fatty acid amide lubricants, fatty acid ester lubricants, fatty acid lubricants, fatty acid metal salt lubricants, and the like. The crystal nucleating agent is not particularly limited, but examples thereof include sorbitols, phosphorus-based nucleating agents, rosins, petroleum resins, and the like. The softener is not particularly limited, but examples thereof include liquid paraffin, mineral oil-based softeners (process oil), and mineral oil-based softeners (process oil) for non-aromatic rubber.

[0046] The antistatic agent is not particularly limited, but examples thereof include cationic antistatic agents, anionic antistatic agents, nonionic antistatic agents, amphoteric antistatic agents, and fatty acid partial esters such as glycerin fatty acid monoesters. The metal deactivator is not particularly limited, but examples thereof include hydrazine-based metal deactivators, nitrogen compound-based metal deactivators, and phosphite-based metal deactivators. The antibacterial or antifungal agent is not particularly limited, but examples thereof include organic compound-based antibacterial or antifungal agents, natural organic antibacterial or antifungal agents, inorganic antibacterial or antifungal agents, and the like. The pigment is not particularly limited, but examples thereof include inorganic pigments and organic pigments. Examples of inorganic pigments include titanium oxide, calcium carbonate, and carbon black. Examples of organic pigments include azo pigments, acid dye lakes, basic dye lakes, and condensed polycyclic pigments.

[0047] In addition, as additives, nitrogen compounds, metal hydroxides, silicone flame retardants, organic alkali metal salts, organic alkaline earth metal salts, borate compounds such as zinc borate, zinc metaborate, barium metaborate, aluminum borate, and sodium polyborate; Silica (silicon dioxide), synthetic amorphous silica (silicon dioxide), aluminum silicate, magnesium silicate, calcium silicate, zirconium silicate, diatomaceous earth and other silicon compounds, Metal oxides such as aluminum oxide, magnesium oxide, barium oxide, titanium oxide, zinc oxide, tin oxide, zirconium oxide, molybdenum oxide, and zirconium-antimony composite oxide; Expandable graphite and the like may be added within a range that does not impair the effects of the invention.

[0048] The additives may be used alone or in combination of two or more. The amount of the additives is not particularly limited as long as the properties of the flame-retardant resin composition are not impaired.

[0049] One embodiment of the flame-retardant resin composition of the present invention consists essentially of components (A) to (D) and optional additives, and may contain other inevitable impurities as long as the effects of the present invention are not impaired. In one embodiment of the flame-retardant resin composition of the present invention, for example, 80 to 100 mass%, 90 to 100 mass%, 95 to 100 mass%, 98 to 100 mass%, or 100 mass% is Components (A) to (D), or It may consist of components (A) to (D) and, optionally, additives.

[0050] One embodiment of the flame-retardant resin composition of the present invention can be produced, for example, by blending components (A) to (D) and, if necessary, additives, and hot melt mixing (kneading). For example, the above components can be blended and kneaded using a Henschel mixer, a Banbury mixer, a single screw extruder, a twin screw extruder, a multi-screw extruder, a co-kneader, or the like. The heating temperature during kneading is usually 160 to 250°C. Alternatively, the above components may be blended and premixed using commonly used equipment (eg, ribbon blender, drum tumbler, etc.) and then kneaded using the above device.

[0051] One embodiment of the flame-retardant resin composition of the present invention may be in the form of pellets or the like.

[0052] One embodiment of the molded article of the present invention can be produced using the above-mentioned flame-retardant resin composition. The preparation can be carried out by, for example, injection molding, injection compression molding, extrusion molding, blow molding, press molding, vacuum molding, foam molding, or the like. One embodiment of the molded article of the present invention can be suitably used in, for example, automobiles, industrial materials, building materials, electronic and electrical equipment, office automation equipment, the machinery field, home appliances, and home appliances (high grade). EXAMPLES

[0053] Examples 1 to 14 and Comparative Examples 1 to 9 [Production of flame-retardant resin composition] The components shown in Tables 1 and 2 were melt-mixed at 200°C and 250 rpm in the blending ratios shown in Tables 1 and 2 (% by mass based on 100% by mass of the total content of components (A) to (C) or parts by mass based on 100 parts by mass of the total content of components (A) to (C)) in a twin-screw extruder PCM-30 (manufactured by Ikegai Corporation) to produce pellets (flame-retardant resin composition).

[0054] The components used are shown below. Component (A) Resin A: J-700GP (Prime Polymer Co., Ltd., homopolypropylene, melt flow rate (MFR) at 230°C: 8.0g / 10min) Resin B: J106MG (Prime Polymer Co., Ltd., homopolypropylene, MFR at 230°C: 15g / 10min) Resin C: J707G (Prime Polymer Co., Ltd., block polypropylene, MFR at 230°C: 30g / 10min)

[0055] (B) Component Natural inorganic filler A: ILF-BAH (manufactured by Asada Flour Milling Co., Ltd., average particle size (D50): 17 μm, talc, moisture: 0.04%, whiteness W value: 92%, apparent specific gravity: 0.4 g / ml, loss on ignition at 500°C: 0.02%) Natural inorganic filler B: Jilin Prov. Lishu Dadingshan Wollastonite (Jilin Province) (manufactured by Hulan Wollastonite Mining Co., Ltd., wollastonite, distribution: 400 mesh (ASTM standard) pass rate 98.2%)

[0056] (C) Component Flame retardant A: CR-900 (manufactured by Daihachi Chemical Industry Co., Ltd., tris(tribromoneopentyl)phosphate, melting point: 182°C, decomposition temperature: 313°C (TGA (thermogravimetric analysis) 1% loss))

[0057] (D) Component Radical generator A: Nofumar BC-90 (NOF Corporation, 2,3-dimethyl-2,3-diphenyl-butane, purity: 86%, compound represented by the following formula, melting point: 80 to 130°C, decomposition temperature: 140°C (TGA (thermogravimetric analysis) 1% loss)) [ka] Radical generator B: CC-P3 (manufactured by United Initiators, poly-1,4-diisopropylbenzene, a compound represented by the following formula, melting point: 105 to 135°C, decomposition temperature: 170°C (TGA 1% loss)) [ka]

[0058] The MFR of component (A) was measured in accordance with ASTM D-1238 (2013) at 230°C and 2.16 kg.

[0059] In component (B), the average particle size of the natural inorganic filler A was measured using a laser diffraction particle size distribution measuring device LA-300 (manufactured by Horiba, Ltd.).

[0060] In the component (B), the distribution of the natural inorganic filler B was measured by the penetration rate through a 400 mesh (ASTM standard). The 400 mesh passing rate was determined by placing a sample on a 400 mesh and sieving it through a vibrating sieve.

[0061] In component (B), the moisture content of the natural inorganic filler A was measured by the Karl Fischer method using a moisture measuring device VA-06 / CA-06 (manufactured by Mitsubishi Chemical Corporation). In the component (B), the whiteness W value of the natural inorganic filler A was measured using an SM Color Computer SM45 (manufactured by Suga Test Instruments Co., Ltd.). In component (B), the apparent specific gravity of the natural inorganic filler A was measured in accordance with JIS K5101. In component (B), the ignition loss at 500° C. of the natural inorganic filler A was measured using a muffle furnace F0610 (manufactured by Yamato Scientific Co., Ltd.) at 500° C. for 3 hours using 1 g of the natural inorganic filler A.

[0062] The melting points of components (C) and (D) were measured using a TGA / DSC1 (manufactured by METTLER TOLEDO) by increasing the temperature from 30° C. to 600° C. at a rate of 20° C. / min in a N2 atmosphere. The decomposition temperatures of components (C) and (D) were measured using TGA / DSC1. The temperature was raised from 30°C to 600°C at a heating rate of 20°C / min in a N2 atmosphere, and the temperature at which the weight decreased by 1% was recorded as the decomposition temperature.

[0063] [Measurement of MFR of flame-retardant resin composition] The MFR of the obtained pellets was measured at 230°C and 2.16 kg in accordance with ASTM D-1238 (2013). The results are shown in Tables 1 and 2.

[0064] [Production of Molded Products] The obtained pellets were dried at 80°C and then molded at 200°C using an injection molding machine ("NEX110III" manufactured by Nissei Plastic Industrial Co., Ltd.) to produce UL test pieces (test pieces for the UL94 test described below) (molded bodies) with thicknesses of 0.8 mm and 1.6 mm, respectively.

[0065] [Measurement of antimony (Sb) content] The obtained pellets and compacts were measured using an EDS (energy dispersive X-ray analysis) device equipped with a JSM-6390LA (manufactured by JEOL Ltd.) at an acceleration voltage of 20 kV. The results are shown in Tables 1 and 2. "-" indicates that the value was below the detection limit (2000 ppm).

[0066] [Flame retardant rating 1 (thickness 0.8 mm)] A vertical flame test (UL94 test) was conducted in accordance with the UL94 standard using a flame retardancy evaluation tester (Atlas, HVUL plastic UL flame test chamber) for the 0.8 mm thick UL test specimens obtained by manufacturing the molded bodies. Specifically, the flame retardancy of the five test specimens was ranked in accordance with the UL94 standard based on the first and second burning times, and whether the cotton ignited or not. The results are shown in Tables 1 and 2.

[0067] [Flame retardant rating 2 (thickness 1.6 mm)] Flame retardancy was evaluated in the same manner as in Evaluation 1, except that a 1.6 mm thick UL test specimen obtained in the production of a molded product was used instead of a 0.8 mm thick UL test specimen. The results are shown in Tables 1 and 2.

[0068] [Table 1]

[0069] [Table 2]

Claims

1. Contains the following components (A) to (D): Substantially free of antimony the content of the component (A) is 52% by mass or more and 94% by mass or less, based on 100% by mass of the total content of the components (A) to (C); the content of the (B) component is 5% by mass or more and 30% by mass or less, based on 100% by mass of the total content of the (A) components, the (B) components, and the (C) components; the content of the (C) component is 0.5% by mass or more and 20% by mass or less, based on 100% by mass of the total content of the (A) components to the (C) components; The content of the (D) component is 0.01 parts by mass or more and 3.0 parts by mass or less based on 100 parts by mass of the total content of the (A) components, the (B) components, and the (C) components. (A) Polypropylene (B) a natural inorganic filler comprising one or more selected from the group consisting of talc and wollastonite; (C) Tris(tribromoneopentyl)phosphate flame retardant (D) A radical generator which is 2,3-dimethyl-2,3-diphenyl-butane or poly-1,4-diisopropylbenzene

2. 2. The flame-retardant resin composition according to claim 1, wherein the melt flow rate at 230° C. of the flame-retardant resin composition is from 0.01 g / 10 min to 100 g / 10 min.

3. 3. The flame-retardant resin composition according to claim 1, wherein the melt flow rate of the component (A) at 230° C. is from 0.01 g / 10 min to 100 g / 10 min.

4. The component (B) is talc, 4. The flame-retardant resin composition according to claim 1, wherein the average particle size of the component (B) is 7 μm or more and 30 μm or less.

5. A molded article produced using the flame-retardant resin composition according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Flame-retardant resin composition

    JP1991179058A

  • Flame retardant polyolefin composition

    JP2002322322A

  • Bromine-based flame retardant composition for plastics

    JP2006070138A

  • Flame-retardant polyolefin woven or knitted fabric and flame-retardant fiber shaped article

    JP2006283206A

  • Flame-retardant material and molded body

    JP2010106221A